Prayer: Personality Forms of Presentation - Predko, Denys (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2021)
The phenomenon of prayer is studied in the context of a dialogue, in which different levels of perception of "Self" are expressed. The article examines the regularities of the emergence and functioning of prayer as communication in which a dialogue unfolds - the existential orientation of personality. It is analyzed, on the one hand, the specificity and role of prayer in the historical genesis, and on the other, its personalization and thematization. Historical forms allow both the process of distinguishing prayer from other linguistic acts of a religious and non-religious nature and to identify the aspects of communication of the religious relationship between "Self" and "You", the personality and the personalized supernatural. The relationship between prayer and magical cult practice has been carried out. It is emphasized that in many primitive communities, prayer took the form of magical incantations and spells, in which the will component was dominant. Moreover, interpersonal communication unfolded as a horizontal connection, due to which there was a transfer of experience, it’s purely practical orientation. Christian prayer, on the other hand, is dominated by communicative ties, which, first, are "woven" in the context of the dominant vertical connection between "Self" and God, and, second, are determined by the interpersonal relationships of the religious community. Depending on the goal pursued by a person, prayers have a different personalistic orientation. However, in general, they all generate meanings aimed both at accumulating experience in overcoming difficult life situations and at personal growth.